Impact of the COVID-19 Pandemic on SME Debt in a Sub-Saharan Context : The Case of Cameroon (Global Journal of Management and Business Research, 2023)
Following the confinement imposed by the Cameroonian authorities after the contamination of some people by the Coronavirus several companies in general and SMEs in particular have experienced great difficulties due to a partial or total cessation of their activities The objective of this study is to evaluate the impact of the Covid-19 pandemic on the indebtedness of Cameroonian SMEs Through statistical and econometric analyses carried out on a sample of 450 Cameroonian SMEs the results obtained highlight the significant influence of the Covid-19 health crisis on the better development of Cameroonian SMEs activities This suggests that the Cameroonian government and or financial partners should provide financial assistance to SMEs in order to alleviate the cash flow difficulties caused by the Covid-19 pandemic
Keywords: pandemic; debt; covid-19; containment; SMEs